Severe pigeon paramyxovirus 1 infection in a human case with probable post-COVID-19 condition - Shujuan Cui; Hui Xiong; Zhaomin Feng; Yanhui Chu; Chengli Que; Jingning Qin; Yang Pan; Kunyao Yu; Lei Jia; Xi Yao; Jiping Liao; Da Huo; et al. (Emerging Microbes and Infections, 2023)
Pigeon paramyxovirus 1 (PPMV-1) is an antigenic host variant of avian paramyxovirus 1. Sporadic outbreaks of PPMV-1 infection have occurred in pigeons in China; however, few cases of human PPMV-1 infection have been reported. The purpose of this article is to report a case of severe human PPMV-1 infection in an individual with probable post-COVID-19 syndrome (long COVID) who presented with rapidly progressing pulmonary infection. The patient was a 66-year-old man who was admitted to the intensive care unit 11 days after onset of pneumonia and recovered 64 days after onset. PPMV-1 was isolated from the patient’s sputum and in cloacal smear samples from domesticated pigeons belonging to the patient’s neighbour. Residual severe acute respiratory syndrome coronavirus 2 was detected in respiratory and anal swab samples from the patient. Sequencing analyses revealed that the PPMV-1 genome belonged to genotype VI.2.1.1.2.2 and had the 112RRQKRF117 motif in the cleavage site of the fusion protein, which is indicative of high virulence. This case of cross-species transmission of PPMV-1 from a pigeon to a human highlights the risk of severe PPMV-1 infection in immunocompromised patients, especially those with long COVID. Enhanced surveillance for increased risk of severe viral infection is warranted in this population.